Leisure-time versus full-day energy expenditure: a cross-sectional study of sedentarism in a Portuguese urban population - Barros Henrique; Santos Ana-Cristina; Gal Diane L (BMC, 2005)
Abstract Background Low physical activity is known to be a potential risk factor for cardiovascular disease. With high prevalence of cardiovascular diseases in the Portuguese urban population, little is known about how sedentary this population is and what factors are associated to sedentary lifestyles. This study's objective was to examine sedentary lifestyles and their determinants through a cross-sectional study. Methods 2134 adults (18 years and older) were interviewed using a standard questionnaire, comprising of social, behavioural and clinical information. Time spent in a variety of activities per day, including: work, household chores, sports, sedentary leisure time and sleep, were self-reported. Energy expenditure was estimated based on the related metabolic equivalent (MET) and time spent in each activity (min/day). Those with less than 10% of energy expenditure at a moderate intensity of 4 METs or higher were categorised as sedentary. The proportion of sedentary people and 95% Confidence Intervals (CI) were calculated, and the magnitude of associations, between sedentary lifestyles and the population characteristics, were computed as age-adjusted odds ratios using logistic regression. Results Sedentarism in both genders during leisure time is high at 84%, however in full day energy expenditure, which includes physical activity at work, sleeping hours and household chores, 79% of males and 86% of females are found to be sedentary. In leisure-time only, increased age is associated with higher odds of being sedentary in both genders, as well as in women with increased BMI. In comparison, in full-day energy expenditure, sedentarism is more likely to occur in those with higher levels of education and in white-collar workers. Conclusions A high prevalence of sedentarism is found in the study participants when measuring leisure-time and full-day energy expenditure. The Portuguese population may therefore benefit from additional promotion of physical activity.